Partial Pulpotomy in Young Permanent Teeth: A Systematic Review and Meta-Analysis - Nicole Camoni; Maria Grazia Cagetti; Silvia Cirio; Marcella Esteves-Oliveira; Guglielmo Campus (MDPI AG, 2023)
The aim of the present systematic review was to evaluate the clinical and radiographic success of partial pulpotomies in deep caries processes or post-eruptive defects in young, vital permanent teeth. Four electronic databases, PubMed, Scopus, Embase, and Google Scholar, were searched, followed by a manual search in the reference lists. Randomized controlled trials evaluating partial pulpotomy with a follow-up period of ≥12 months were included. A meta-analysis using a random effects model was performed. A total of 3127 articles were retrieved, and after duplicate removal, 2642 were screened by title and abstract; 1 additional article was found during the manual search, and 79 were identified. Finally, six papers were included in the review. Regardless of the partial pulpotomy modalities or material used, there were no significant differences between clinical and radiographic success rates (cumulative success rate 91.8-92.3%). Five studies were included in the meta-analysis that did not indicate any statistically significant differences in success rates when mineral trioxide aggregate was compared to other materials (95% confidence interval: 0.239 to 1.016; p = 0.055). The present research systematically evaluates the evidence and summarizes the available data on partial pulpotomy in young permanent teeth. Given its high clinical and radiographic success rate, partial pulpotomy should be considered when vital pulpal therapy needs to be performed in highly damaged young permanent teeth, as this procedure provides a biological benefit and allows more invasive endodontic treatments to be postponed.